Use of Electronic Clinical Decision Support and Hard Stops to Decrease Unnecessary Thyroid Function Testing. Issue 1 (28th April 2017) - Dalal, Sonia; Bhesania, Siddharth; Silber, Steven; Mehta, Parag
Abstract : NewYork-Presbyterian Brooklyn Methodist Hospital embarked on a Zero Unnecessary Study (ZEUS) initiative, whereby all aspects of clinical care were evaluated and strategies were implemented to mitigate waste. An opportunity was found in regards to thyroid function testing. It has been shown that certain TFTs are ordered far more often than clinically indicated. Free T3 (fT3) and Free T4 (fT4) are only indicated when the TSH is abnormal in the inpatient setting, with rare exceptions. Thus, a clinical algorithm for Clinical Decision Support (CDS) and Hard Stops (HS) were incorporated into the Electronic Medical Record (EMR) to prevent fT3 or fT4 to be ordered without an abnormal TSH, with certain predefined exceptions. In addition, a reflex rule was built which automatically orders (reflex) fT3 and fT4 if the TSH is abnormal. The pre and post-intervention ratios of fT3 and fT4 orders per total TSH orders were analyzed. Pre-intervention data revealed that fT4 was the most frequently ordered TFT laboratory test on admission, after TSH. Post-Intervention, there was a decrease in the ratio of fT4 to TSH orders (fT4/TSH) of 35.2%, from 44.6% to 28.9%. The percentage of fT4 ordered due to abnormal TSH increased by 126.1%, from 36.8% to 83.2%. The fT3 to TSH ordering ratio similarly decreased by 55.2%, from 6.2% to 2.9%. The decreases in both fT3/TSH and fT4/TSH ratios were statistically significant. Any unnecessary orders are a burden on healthcare. It is now possible to achieve goals that were not previously thought to be possible because of advancement in medicine and technology. By making small changes and saving costs, we can target our energy and resources toward effectively treating patients.